BEBERAPA FAKTOR YANG MEMPENGARUHI MINAT WUS (WANITA USIA SUBUR) DALAM MELAKUKAN PEMERIKSAAN IVA (INSPEKSI VISUAL DENGAN PULASAN ASAM ASETAT) DI DESA PANGEBATAN KECAMATAN KARANGLEWAS KABUPATEN BANYUMAS TAHUN 2011 - Rahma, Rina Arum; Prabandari, Fitria (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2012)
IVA (Visual Inspection with Acetic Acid outward appearance) is one of the alternative methods of cervical cancer screening. Indonesian women's awareness for early detection of cervical cancer on a regular basis is still low. Coverage of early detection in Indonesia <5%, so many cases of cervical cancer found at an advanced stage which often causes death. There are several factors that support the WUS (women of childbearing age) perform IVA: education, knowledge, and family support.Objectives: Knowing the factors that influence interest in conducting the examination IVA WUS in the Village District Pangebatan Karanglewas Banyumas.Method: This type of research is the Correlation studies using the cross-sectional approach. Samples are WUS totaling 100 respondents, how to capture using stratifed random sampling, data analysis using statistical test Chi – Square. Results: The majority of basic-educated respondents (48%), Chi-Square test statistics obtained 0.019 p <0.05 no significant relationship between education with an interest in conducting the examination IVA WUS, contingency value of 0.343, the closeness of the relationship is weak. The majority of respondents had less knowledge (46%), Chi - Square obtained p 0, 018 <0.05 no significant relationship between knowledge with an interest in conducting the examination IVA WUS, contingency value 0.346, the closeness of the relationship is weak. The majority of respondents have family support are (41%), Chi - Square obtained p 0, 001 <0.05 no significant relationship between family support with an interest in conducting the examination IVA WUS, contingency value 0.439, the closeness of the relationship is weak.Conclusion: There is a significant relationship between education, knowledge, support families with an interest in conducting the examination IVA WUS, Most is the closeness of the relationship of family support.Keywords: Education, Knowledge, Family Suppor, WUS,IVA